Elevated C-Reactive Protein in Asymptomatic Crohn's Disease Patients: Listen to the Sound of Silence. Issue 3 (March 2017) - Pagnini, Cristiano; Mariani, Maria Benedetta; Corleto, Vito Domenico; Delle Fave, Gianfranco
Abstract : Article first published online 31 January 2017.